RNA-sequencing studies suggest that microRNAs and alternative splicing of pre-mRNAs modulate immune and inflammatory responses in Holstein cattle infected with Mycobacterium avium subsp. paratuberculosis - Badia-Bringué, Gerard; Alonso-Hearn, Marta (Frontiers in Immunology, 2025)
RNA-Sequencing (RNA-Seq) studies using bovine samples from Mycobacterium avium subsp. paratuberculosis (MAP)-infected animals have identified a range of differentially expressed mRNAs with potential as biomarkers for MAP infection. As bioinformatic tools continue to develop, microRNAs (miRNAs) and alternative splicing (AS) have emerged as important contributors to host responses during infections. Although RNA-Seq enables AS analysis, most transcriptomic studies still emphasize gene-level expression due to the complexity of AS workflows, the need for deeper sequencing, and incomplete transcript annotations, even in humans. Nevertheless, interest in AS is growing, driven by its recognized role in tissue-specific functions and disease mechanisms. Recent findings have revealed distinct miRNAs and AS profiles in MAP-infected cattle compared to uninfected cows, indicating that post-transcriptional regulatory mechanisms are altered during MAP infection. In this comprehensive review, we examine critical aspects of post-transcriptional regulation in the context of MAP infection. We focus on recent studies investigating miRNAs and AS profiles, highlighting their roles in modulating immune responses and their potential as novel diagnostic biomarkers. Notably, overlapping mechanisms involving miRNAs and AS have been identified in paratuberculosis and in several human diseases, suggesting conserved pathways of host-pathogen interaction and immune regulation.